(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Demonetization is when a currency note of a particular denomination ceases to be a legal tender. It can also be referred to as scrapping or phasing out of certain currency notes. In India, every household has included demonetization in their daily routine since 8th November 2016, time when the government pulled the old Rs500 and Rs1000 notes out of circulation. One of the major questions that arise in the mind of every individual is that what led to Demonetization? There are 3 major reasons for the same:- To curb black money in the economy. To encourage cashless transactions. To reduce corruption practices like Hawala. Every cause has pros and cons, so when we talk about Demonetization it itself has some pros and cons. But, the immediate execution of this move has created more negative outcomes than positive as they are largely directed onto the common man. Those who do not have easy access to banks and post offices are finding it difficult to accept this change. Till date, new currency notes continue to be in short supply, causing difficulties for people to carry out day-to-day transactions. The motive behind this sudden execution of Demonetization in India was to get hold of Black money hoarders but it has led to many shortcomings, if this step would have been made at the later stages, the results would have been more positive. In this research paper, we want to discuss the impact of recent demonetization on the Indian system